The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/acn3.51687
|View full text |Cite
|
Sign up to set email alerts
|

The clinical spectrum of SMA‐PME and in vitro normalization of its cellular ceramide profile

Abstract: Objective The objectives of this study were to define the clinical and biochemical spectrum of spinal muscular atrophy with progressive myoclonic epilepsy (SMA‐PME) and to determine if aberrant cellular ceramide accumulation could be normalized by enzyme replacement. Methods Clinical features of 6 patients with SMA‐PME were assessed by retrospective chart review, and a literature review of 24 previously published cases was performed. Leukocyte enzyme activity of acid ceramidase was assessed with a fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Hence, the preservation of the function of these pathways may have contributed to the improved health span in aged mice and increased life span in worms treated with myriocin. This is consistent with previous reports showing that ceramides are key signaling contributors to the pathogenesis of various proteotoxic neuromuscular diseases such as Parkinson's disease, progressive cerebello-cerebral atrophy type 2, Huntington’s disease, spinal muscular atrophy, and valosin-containing protein (VCP)–associated inclusion body myopathy ( 43 , 48 50 ). Given the known effects of ceramides on human pathophysiology, such as in insulin resistance, dyslipidemia, and cardiovascular diseases ( 19 22 ), it will be of interest to study whether ceramide dysregulation also causes proteotoxicity in these obesity-fueled disorders.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the preservation of the function of these pathways may have contributed to the improved health span in aged mice and increased life span in worms treated with myriocin. This is consistent with previous reports showing that ceramides are key signaling contributors to the pathogenesis of various proteotoxic neuromuscular diseases such as Parkinson's disease, progressive cerebello-cerebral atrophy type 2, Huntington’s disease, spinal muscular atrophy, and valosin-containing protein (VCP)–associated inclusion body myopathy ( 43 , 48 50 ). Given the known effects of ceramides on human pathophysiology, such as in insulin resistance, dyslipidemia, and cardiovascular diseases ( 19 22 ), it will be of interest to study whether ceramide dysregulation also causes proteotoxicity in these obesity-fueled disorders.…”
Section: Discussionsupporting
confidence: 93%
“…Zielonka et al showed that a higher residual activity of aCDase is associated with later onset and longer survival of Farber patients [ 27 ]. A similar pattern seems to be true also for SMA-PME which is an ultrarare (Prevalence: < 1/1 000 000 ) [ 28 – 30 ] childhood neurological condition leading to muscle weakness and atrophy. It also manifests seizures and uncontrollable myoclonic epilepsy [ 8 ].…”
Section: Discussionmentioning
confidence: 57%
“…In a study of three Iranian patients, exome sequencing in combination with testing to evaluate survival motor neuron 1 (SMN1) and 2 (SMN2) copy numbers to rule out SMA revealed new causative variants in ASAH1 [90]. In a study of six new patients with the hallmark features of SMA-PME-namely lower motor neuron disease, tremor, and ataxia without the triad of FD-five of the six patients carried at least one of the known SMA-PME variants in ASAH1 [92]. In the same study, a review of 30 cases showed that patients homozygous for the common c.125C>T variant presented in the first decade of life with limb-girdle weakness, while patients with the c.456A>C variant experienced sensorineural hearing loss.…”
Section: Diagnostic and Phenotypic Advancesmentioning
confidence: 99%